Eksistensi Peraturan Daerah Responsif-Partisipatif: Konkretisasi Politik Hukum yang Demokratis-Populis di Daerah - Leonardy, Josep; Usfunan, Yohanes (Juris Prima: Jurnal Inovasi Hukum dan Kebijakan, 2025)
Background: The responsive-participatory approach in forming Regional Regulations involves democratic engagement, particularly the active participation of the community and direct stakeholders at all stages, as outlined in Law Number 12 of 2011. Objective: This participatory process enhances the effectiveness of Regional Regulations, as community acceptance, stemming from their involvement, is crucial for meeting legal needs rather than relying on enforcement coercion. Method: This study utilises normative legal research, applying laws through statutory and conceptual approaches. Results: The findings emphasise that a democratic political configuration fosters community involvement in drafting Regional Regulations, reflecting a democratic-populist legal agenda. Conclusion and Recommendations: It concludes that regulations developed without community input tend to be authoritarian and face rejection, whereas active participation fosters compliance with higher laws, supports law enforcement, and promotes democracy. Recommendations include the establishment of a Regional Regulation on Community Participation to strengthen legal clarity and commitment, ensuring that the community is involved in the legislative process through existing provisions.